CPU86017-RS attenuate hypoxia-induced testicular dysfunction in mice by normalizing androgen biosynthesis genes and pro-inflammatory cytokines - Zhang Guo-lin; Yu Feng; Dai De-zai; Cheng Yu-si; Zhang Can; Dai Yin (Acta Pharmacologica Sinica, 2016)
Aim: Downregulation of androgen biosynthesis genes StAR (steroidogenic acute regulatory) and 3β-HSD (3β-hydroxysteroid dehydrogenase) contributes to low testosterone levels in hypoxic mice and is possibly related to increased expression of pro-inflammatory cytokines in the testis. The aim of this study is to investigate the effects of CPU86017-RS that block Ca2+ influx on hypoxia-induced testis insult in mice. Methods: Male ICR mice were divided into 5 groups: control group, hypoxia group, hypoxia group treated with nifedipine (10 mg/kg), hypoxia groups treated with CPU86017-RS (60 or 80 mg/kg). Hypoxia was induced by placing the mice in a chamber under 10%±0.5% O2 for 28 d (8 h per day). The mice were orally administered with drug in the last 14 d. At the end of experiment the testes of the mice were harvested. The mRNA and protein levels of StAR, 3β-HSD, connexin 43 (Cx43), matrix metalloprotease 9 (MMP9), endothelin receptor A (ETAR) and leptin receptor (OBRb) were analyzed using RT-PCR and Western blotting, respectively. The malondialdehyde (MDA), lactate dehydrogenase (LDH), succinate dehydrogenase (SDH) and acid phosphatase (ACP) levels were measured using biochemical kits. Serum testosterone concentration was measured with radioimmunoassay. Results: Hypoxia significantly increased the MDA level, and decreased the LDH, ACP and SDH activities in testes. Meanwhile, hypoxia induced significant downregulation of StAR and 3β-HSD in testes responsible for reduced testosterone biosynthesis. It decreased the expression of Cx43, and increased the expression of MMP9, ETAR and OBRb, leading to abnormal testis function and structure. These changes were effectively diminished by CPU86017-RS (80 mg/kg) or nifedipine (10 mg/kg). Conclusion: Low plasma testosterone level caused by hypoxia was due to downregulation of StAR and 3β-HSD genes, in association with an increased expression of pro-inflammatory cytokines. These changes can be alleviated by CPU86017-RS or nifedipine.